The Deep Learning with Keras Workshop : An Interactive Approach to Understanding Deep Learning with Keras, 2nd Edition /: An Interactive Approach to Understanding Deep Learning with Keras, 2nd Edition. (2020) - Moocarme, Matthew; Abdolahnejad, Mahla; Bhagwat, Ritesh
No abstract available